Validation of an ultra high performance liquid chromatography–tandem mass spectrometry method for detection and quantitation of 19 endocrine disruptors in milk. (February 2015) - Wielogórska, E.; Elliott, C.T.; Danaher, M.; Chevallier, O.; Connolly, L.
Abstract: An endocrine disruptor (ED) is an exogenous compound that interferes with the body's endocrine system. Exposure to EDs may result in adverse health effects such as infertility and cancer. EDs are composed of a vast group of chemicals including compounds of natural origin such as phytoestrogens or mycotoxins and a wide range of man-made chemicals such as pesticides. Synthetic compounds may find their way into the food chain where a number of them can biomagnify. Additionally, processing activities and food contact materials may add further to the already existing pool of food contaminants. Thus, our diet is considered to be one of the main exposure routes to EDs. Some precautionary legislation has already been introduced to control production and/or application of some persistent organic pollutants with ED characteristics. However, newly emerging EDs with bioaccumulative properties have recently been reported to appear at lower tiers of the food chain but have not been monitored at the grander scale. Milk and dairy products are a major component of our diet, thus it is important to monitor them for EDs. However, most methods developed to date are devoted to one group of compounds at a time. The UHPLC–MS/MS method described here has been validated according to EC decision 2002/657/EC and allows simultaneous extraction, detection, quantitation and confirmation of 19 EDs in milk. The method calibration range is between 0.50 and 20.0 μg kg −1 with coefficients of determination above 0.99 for all analytes. Precision varied from 4.7% to 23.4% in repeatability and reproducibility studies. Established CCα and CCβ values (0.11–0.67 μg kg −1 ) facilitate fast, reliable, quantitative and confirmatory analysis of sub μg kg −1 levels of a range of EDs in milk. Highlights: Milk should be assessed for contamination with endocrine disruptors. A reliable UHPLC–MS/MS method was developed for screening of endocrine disruptors. Developed method allows screening for sub μg kg −1 levels of endocrine disruptors in milk.